Evaluating the Temporal Location of Feedback: Providing Feedback Following Performance vs. Prior to Performance. Issue 2 (3rd April 2017) - Aljadeff-Abergel, Elian; Peterson, Stephanie M.; Wiskirchen, Rebecca R.; Hagen, Kristin K.; Cole, Mariah L.
ABSTRACT: In order to make feedback as effective as possible, it is important to understand its function in the three-term contingency (TTC) and the impact of various factors involved in delivering feedback. Timing of feedback is one factor that can affect the impact of feedback on learner's behavior. An analysis of timing of feeback may help us getting closer to better understanding how feedback functions in the TTC. The purpose of this study was to evaluate the effects of feedback at different temporal locations. Specifically, feedback was provided either immediately (a) after a teaching session or (b) before the following teaching session, on teaching performance of undergraduate psychology students. The results indicated that feedback provided before the teaching session was more effective in improving teaching skills than feedback that was provided after the session. These findings suggest that feedback may function primarily as an antecedent to future performance and not necessarily as a consequence for past performance. However, the behavioral mechanism that explains these results is not yet clear. Future studies should investigate this further by manipulating the content of feedback prior to the teaching performance.